Gambaran Pengetahuan dan Sikap Terkait Jajanan Sehat pada Siswa SMP Negeri 28 Kota Padang - Riska Rusydi; Fitratur Rahmah Agustina (Lembaga Pengembangan Kinerja Dosen, 2026)
Snacks are one of the primary food sources frequently consumed by school-aged adolescents. Choosing snacks that do not meet food safety and balanced nutrition principles may increase the risk of various health problems. Knowledge and attitudes are important factors influencing adolescents' healthy snack choices. This study aimed to describe the knowledge and attitudes of adolescents regarding healthy snacks at SMP Negeri 28 Padang. This study employed a quantitative descriptive design with a cross-sectional approach. The study involved 56 students selected using a purposive sampling technique. Data were collected using a questionnaire that had been tested for validity and reliability. The data were analyzed using univariate analysis and presented as frequency distributions and percentages. The results showed that 13 respondents (23.3%) had poor knowledge regarding healthy snacks, while 17 respondents (30.4%) had unfavorable attitudes toward healthy snacks. Therefore, schools are expected to optimize nutrition education programs, strengthen the School Health Unit (UKS) activities, and continuously monitor healthy school canteens to improve students' knowledge, foster positive attitudes, and encourage healthy snack selection behaviors among adolescents.